New data about the fauna of Geometrinae (Lepidoptera, Geometridae) of State national natural park «Kolsai koldery» and adjacent areas (Experimental biology, 2015)
Nine species of geometrid moths are discussed in the paper (Thetidia smaragdaria volgaria Guenée, Thetidia correspondens Alphéraky,Thetidia fulminaria Leberer, Hemistola chrysoprasaria lissas Prout, Thalera fimbrialis Scopoli, Chlorissa viridata Linnaeus, Dyschloropsis impararia Guenée, Phaiogramma etruscaria Zeller, Microloxia herbaria advolata Eversmann) from them three species (Thalera fimbrialis Scopoli, Dyschloropsis impararia Guenée, Phaiogramma etruscaria Zeller) are new for SNNP «Kolsai koldery» and adjacent areas, is received new materials on bioecology. On each species are provided information on the distribution, flight butterflies and fodder plants of caterpillars. Zoogeographical structure of the studied fauna of Geometrinae: Transpalearctic steppe species, Mediterranean steppe species, Turanian species, Eurasian species, Palearctic species,
Keywords: Geometrinae; Lepidoptera; Geometridae; DNA barcoding; bioecology; zoogeography